PERANAN APLIKASI KOMPUTER DALAM PENGEMBANGAN USAHA PERDAGANGAN - Azwar Rahmat (STIESNU Bengkulu, 2019)
Abstract Computer technology is a set of facilities consisting of hardware and software which in practice is directed to support and improve the quality of goods selling activities. With the existence of a computer application, the activities of buying and selling goods can be easily monitored simultaneously. Using technology / computer applications can help trade business activities such as using E-Commerce and M-Commerce services in helping the trading process. Because if you use this internet service, the trading process does not require a long time or hours and can trade with a very short time. The presence of computer technology provides many benefits for trade entrepreneurs, such as being able to promote goods, stabilize inventory, ease complex business activities and produce information that can be trusted, relevant, timely, complete, understandable, and tested in the context of planning, controlling and taking Management decision. In addition, the efficiency of business operations and business performance can also be improved. So that businesses can survive in the information age and be able to face global market competition. In addition to generating benefits, the development of information technology can also have a number of negative impacts on businesses, such as the closing of employment opportunities, the emergence of resistance to change and the emergence of information technology crimes that can harm businesses. Keywords: Role of computer applications, development of trading businesses Abstrak Teknologi komputer merupakan seperangkat fasilitas yang terdiri dari perangkat keras dan perangkat lunak yang dalam prakteknya diarahkan untuk mendukung dan meningkatkan kualitas kegiatan penjualan barang. Dengan adanya aplikasi komputer kegiatan jual beli barang dapat dengan mudah pefrmantauan secara bersamaan. Dengan menggunakan teknologi/aplikasi komputer dapat membatu kegiatan usaha perdagangan seperti menggunakan layanan E-Commerce dan M-Commerce dalam membatu proses berdagang. Karena jika menggunakan layanan internet ini maka proses perdagangan tidak membutuhkan waktu yang lama atau berjam-jam dan bisa melakukan perdagang dengan waktu yang sangat singkat. Kehadiran teknologi komputer memberikan banyak manfaat bagi pengusaha dagang, seperti mampu mempromosikan barang, menstabilkan persediaan barang, meringankan aktivitas bisnis yang kompleks serta menghasilkan informasi yang dapat dipercaya, relevan, tepat waktu, lengkap, dapat dipahami, dan teruji dalam rangka perencanaan, pengendalian dan pengambilan keputusan manajemen. Selain itu efisiensi operasi usaha dan kinerja usaha juga dapat ditingkatkan. Sehingga usaha dapat tetap bertahan dalam era informasi serta mampu menghadapi persaingan pasar global. Selain menghasilkan manfaat, perkembangan teknologi informasi juga dapat menimbulkan beberapa dampak negatif bagi usaha, seperti tertutupnya kesempatan kerja, timbulnya resistance to change serta timbulnya kejahatan-kejahatan teknologi informasi yang dapat merugikan usaha. Kata Kunci: Peranan aplikasi komputer, pengembangan usaha dagang